The performance The Influence of Employee Engagement, Work Discipline and Transformational Leadership Style of Village Heads on the Performance of Village Apparatus with Organizational Commitment as an Intervening Variable (Survey of Village Apparatus in Cidahu District, - Syakiroh; Harjadi, Dikdik; Djuniardi, Dede (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This research phenomenon is oriented towards the performance of village apparatus in Cidahu District, Kuningan Regency. The population of this study was all village apparatus in Cidahu District, Kuningan Regency, totaling 135 employees. Given the relatively small population, all populations were used as samples in this study, totaling 135 village apparatus in Cidahu District, Kuningan Regency. The results of the study were that employee engagement had a positive and insignificant effect on organizational commitment. Work discipline and transformational leadership style of the village head had a positive and significant effect on organizational commitment. Employee engagement and work discipline had a positive and significant effect on the performance of village apparatus. The transformational leadership style of the village head had a negative and insignificant effect on the performance of village apparatus. Organizational commitment had a positive and insignificant effect on the performance of village apparatus. Organizational commitment is unable to mediate the influence of employee engagement, work discipline and transformational leadership style on the performance of village officials.